2019
DOI: 10.1103/physrevlett.123.020604
|View full text |Cite
|
Sign up to set email alerts
|

Loop Corrections in Spin Models through Density Consistency

Abstract: Computing marginal distributions of discrete or semi-discrete Markov Random Fields (MRF) is a fundamental, generally intractable, problem with a vast number of applications on virtually all fields of science. We present a new family of computational schemes to calculate approximately marginals of discrete MRFs. This method shares some desirable properties with Belief Propagation, in particular providing exact marginals on acyclic graphs; but at difference with it, it includes some loop corrections, i.e. it tak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…O 2 N ): for very small systems the computation can be performed explicitly but for larger (and often more interesting) systems one may rely on a Monte Carlo Markov Chain (MCMC) estimate that, if performed at each update of the parameters, can be time demanding. We propose in the following an analytic expression of the target model parameters such that the maximum likelihood equations in ( 6) is satisfied, when the model statistics is evaluated by the Density Consistency approximation [28].…”
Section: Problem Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…O 2 N ): for very small systems the computation can be performed explicitly but for larger (and often more interesting) systems one may rely on a Monte Carlo Markov Chain (MCMC) estimate that, if performed at each update of the parameters, can be time demanding. We propose in the following an analytic expression of the target model parameters such that the maximum likelihood equations in ( 6) is satisfied, when the model statistics is evaluated by the Density Consistency approximation [28].…”
Section: Problem Setupmentioning
confidence: 99%
“…Among all the possible choices, in [28] the authors found that any scheme satisfying µi Σii = atanh x i q (ij) gives exact marginalization on acyclic graphs (trees). They then constructed a set of reasonable matching conditions to close the set of update equations (note that in each approximate factor φ ij (x i , x j ) five parameters have to be determined):…”
Section: Closures and Update Schemementioning
confidence: 99%
See 2 more Smart Citations
“…where in the last step we restricted the structure of the prior P (w) := N i=1 ψ i (w i ) to a factorized form, although more general structures can be considered, e.g. as in [34]. In this work, we have considered the so-called spike-and-slab prior [26]:…”
Section: Expectation Propagationmentioning
confidence: 99%